Abdominal Total Hysterectomy: The Modified Aldridge's Procedure with Noda's Method - Watanabe, Yoh (The Surgery Journal, 2019)
Although laparoscopic surgery or robotic surgery has recently been the main procedure adopted for managing benign uterine tumors, abdominal total hysterectomy must still be learned as a basic surgical skill for obstetricians and gynecologists. Total hysterectomy is divided into two types: the extrafascial and intrafascial approaches. Intrafascial hysterectomy, represented by the Aldridge's method, is a useful and safe procedure for treatment when the patient has no cervical malignancy, including cervical intraepithelial neoplasia. Furthermore, the intrafascial approach is safely performed even in patients with firm adhesion in the Douglas's pouch and/or around the uterine cervix due to endometriosis, pelvic inflammatory diseases, or a history of intrapelvic surgery. The intrafascial approach can also effectively prevent descent of the vaginal stump after hysterectomy via the partial preservation of the uterine retinaculum. Although the Aldridge's method was originally reported to start via an intrafascial approach at the position of the internal cervical os using scissors, Dr. Kiichiro Noda created a modified version of the procedure that increases its ease and safety by changing the position and management of the parametrial tissue including the uterine artery. The details of this modified Aldridge's procedure using Noda's method are explained below.
Keywords: abdominal hysterectomy; intrafascial method; Aldridge's procedure; gynecologic surgery; benign tumor